SOME PLANKTONIC FORAMINIFERA FROM THE GULF OF MANNAR - Hamsa, K M S Ameer; Nammalwar, P (Indian Journal of Fisheries, 2011)
Studies 'Of p~an~tonic for,aminifexa in deep se:a floor hav'e been made byStabbings (1939), Cushman and Henbest (1940) and Wiseman: and Ovey(1950). Our knowledge .on the ptanktonic foraminifera in Indi1an watexs is veryme:agre l~thOUgh consider,able work !has been doOne .on tihesystemaJtics. l'he pres,entpaper recQrds :sev,en species of planktonic foram~nifera for the fuist time fromIndian waters. 1'he material used in this study was coHooted at a depth of 180fatihoms off Mandapam, Gulf of Mannar